Perovskite Solar Cells: A Cryogenic Process for Antisolvent‐Free High‐Performance Perovskite Solar Cells (Adv. Mater. 44/2018). Issue 44 (5th November 2018) - Ng, Annie; Ren, Zhiwei; Hu, Hanlin; Fong, Patrick W. K.; Shen, Qian; Cheung, Sin Hang; Qin, Pingli; Lee, Jin‐Wook; Djurišić, Aleksandra B.; So, Shu Kong; Li, Gang; Yang, Yang; et al.
Abstract : A novel cryogenic process, described by Charles Surya and co‐workers in article number1804402 has universal applicability to grow organometal halide perovskites. A cryogenic temperature inhibits premature coalescence of nuclei into large crystallites, decoupling nucleation and crystallization phases. The enhanced control over the growth process yields excellent film and high‐performance solar cells.